APPLICATION OF THE RAD METHOD TO THE DEVELOPMENT OF BARBERSHOP TRANSACTION REPORT INFORMATION SYSTEM USING VISUAL FOXPRO 9.0 - Hening Hendrato; Linda Wahyu Widianti; Ani Rachmaniar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Barbershop business activity is a form of small and medium enterprises (UKM) currently growing rapidly owned by a group of Indonesian people. Barbershop business is usually carried out in an open place that is easy for potential customers to find. Barbershop activities provide services to customers in the form of haircuts, mustaches and head washing. The period when customers use barbershop services is very continuous, periodically according to the age of hair growth. There are so many transactions in the barbershop business that a good information system is needed to calculate the profits earned in a certain period. Based on this information, this research builds an accurate and reliable information system. The developed system provides a solution to obtain overall transaction report information in a period of time so that total profit information can be well known. The development of this system uses the Rapid Application Development Method to facilitate application development. The development of a transaction report system and profit reports for barbershop business activities is translated using Microsoft Visual Foxpro 9.0 software. The developed information system answers problems in the financial reports of barbershop activities to become more structured.